Germination and emergence of trumpet flower (tecoma stans) under different environmental conditions - Reis,F.C. (2014)
The aim of this work was to analyze the effect of temperature and light intensity on trumpet flower seed germination, as well as the effect of seeding depth on its emergence. To study the influence of temperature, nine temperature intervals were evaluated, ranging from 15.0 to 40.0 ºC. A randomized block design experiment was used with five replications and 20 seeds per replication, and performed twice. To evaluate light intensity on seed germination, a randomized experimental design was used with eight replications and 25 seeds per replication. The treatments applied were: photoperiod with temperature alternation; photoperiod with constant temperature; darkness with temperature alternation; and darkness with constant temperature. The photoperiod consisted of 8 hours of light and 16 hours of darkness, and the constant temperature was 25 ºC. The treatments with temperature alternations were established with 8 hours at 30 ºC, and 16 hours at 20 ºC. Germination was assessed daily to calculate the total percentage of germination as well as the Germination Velocity Index (GVI). To study the influence of seeding depth on plant emergence, 25 seeds were seeded at 0, 20, 40, and 80 mm in pots with sieved soil. The experiment was arranged in a randomized block design with four replications. Seedling emergence was monitored daily until the 15th day after seeding. After that period, the total percentage of emergence was calculated for each experimental unit, as well as the Emergence Velocity Index (EVI). Formation of normal seedlings and the Germination Velocity Index were different among temperatures and higher germination percentages were observed between 20.3 ºC and 37.5 ºC. Tecoma stans seedlings did not germinate when planted at 40 and 80 mm depth. However, the seedlings placed on the soil surface had an emergence percentage of 72. At 20 mm depth, the emergence rate was 31%.